A real‐world experience of subcutaneous and transvenous implantable cardiac defibrillators—comparison with the PRAETORIAN study. Issue 2 (21st February 2022) - Khanra, Dibbendhu; Hamid, Abdul; Patel, Peysh; Tomson, John; Abdalla, Ahmed; Khan, Nasrin; Dowd, Rory; Chandan, Nakul; Osagie, Christopher; Jinadu, Tomilola; Velu, Selvakumar; Arya, Anita; et al.
Abstract: Background: PRAETORIAN is the first randomized controlled trial that demonstrated the noninferiority of subcutaneous ICD (S‐ICD) in comparison with transvenous ICD (TV‐ICD). We retrospectively reviewed electronic records of patients with ICD implanted over the past 6 years, with the primary objective to compare our real‐world single tertiary center experience with the randomized data from the PRAETORIAN study. Methods: Seventy S‐ICD patients were compared with 197 TV‐ICD patients, from July 2014 to June 2020 retrospectively, over a median period of 1304 days (296–2451 days). Primary composite endpoints included inappropriate shocks and device‐related malfunctions. Results: Patients with S‐ICD implantation were younger than those who received TV‐ICD (mean, 49.7 years vs 63.9 years, p  < .001). About 31.4% of S‐ICDs were implanted for secondary prevention, and 58.6% of S‐ICD patients had ischemic cardiomyopathy (ICM) with a median left ventricular ejection fraction of 32.5% (range: 10–67%). S‐ICDs and TV‐ICD had statistically similar inappropriate shocks (4.3% vs 4.6%, p  = .78), device‐related complications (11.4% vs 9.1%, p  = .93), and the overall primary endpoints (15.7% vs 13.7%, p  = .68). The findings remained the same even after age and gender adjustments and time‐dependent analysis. Conclusion: Although single‐center experience with a small number of S‐ICD patients, results of the PRAETORIAN study has been replicated in our real‐world experience of S‐ICD and TV‐ICD implantations across diverse etiologies, indications, and age groups confirming the comparable performance of S‐ICD and TV‐ICD when implanted in selected patients. Abstract : PRAETORIAN is the only randomized controlled trial demonstrating noninferiority of S‐ICD over traditional TV‐ICD with respect to inappropriate shocks and device‐related complications; however, the proportion of secondary prevention ICD was low. In the real‐world experience of TV‐ICD and S‐ICD implantations over 6 years, in a set of patients without indications for brady pacing, ATP, or cardiac resynchronization, inappropriate shocks and device‐related complications were found to be comparable replicating findings of PRAETORIAN study despite a high proportion of secondary prevention ICD patients. In carefully selected patients, acute and long‐term safety and efficacy of S‐ICD is similar to TV‐ICD across diverse age groups, indications, and etiology. Guidelines should reconsider the recommendation for S‐ICD among PRAETORIAN‐like patients.